2016
DOI: 10.1590/0103-8478cr20140812
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade genética de germoplasma tradicional de feijoeiro comum na região de Cáceres-MT

Abstract: RESUMO O presente trabalho foi conduzido na unidade experimental da Empresa Mato-Grossense de Pesquisa, Assistência Técnica e Extensão Rural (Cáceres-MT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
(7 reference statements)
2
2
0
4
Order By: Relevance
“…The number of common bean cultivars contained in each group ranged from one (groups 6 and 7) to seven (groups 1 and 2). Groups 1 and 2 included a higher number of cultivars, confirming a trend frequently reported in the literature of a higher number of common bean cultivars being concentrated in the first two groups when genetic divergence is analyzed by Tocher's method (GONÇALVES et al, 2016;LIMA et al, 2012;MAZIERO;CASAGRANDE, 2017;PEREIRA et al, 2019;SANTOS et al, 2019). However, in all of these studies, Tocher's method showed to be efficient in the formation of homogeneous groups in relation to the evaluated agronomic traits.…”
Section: Analysis Of Genetic Divergence For Plant Architecture Traits...supporting
confidence: 84%
“…The number of common bean cultivars contained in each group ranged from one (groups 6 and 7) to seven (groups 1 and 2). Groups 1 and 2 included a higher number of cultivars, confirming a trend frequently reported in the literature of a higher number of common bean cultivars being concentrated in the first two groups when genetic divergence is analyzed by Tocher's method (GONÇALVES et al, 2016;LIMA et al, 2012;MAZIERO;CASAGRANDE, 2017;PEREIRA et al, 2019;SANTOS et al, 2019). However, in all of these studies, Tocher's method showed to be efficient in the formation of homogeneous groups in relation to the evaluated agronomic traits.…”
Section: Analysis Of Genetic Divergence For Plant Architecture Traits...supporting
confidence: 84%
“…The lowest CCC was obtained in the UPGMA cluster analysis performed with data obtained in the 2016 rainy (0.5591) and the largest CCC was found with data obtained in the 2017 dry (0.9335) season crops (Figure 1), all of which were signi cant at 1% probability by the t test. A similar amplitude of variation was observed for CCC values obtained in the UPGMA cluster analysis, considering agronomic and/or morphological traits evaluated in one (Gonçalves et al 2014(Gonçalves et al , 2016, two (Arteaga et al 2019) and three (Cabral et al 2011) experiments with different common bean genotypes. The closer to one the CCC value, the greater the adjustment between the cophenetic matrix and the dissimilarity matrix based on the Mahalanobis' generalized distance, resulting in greater cluster reliability (Cabral et al 2011).…”
Section: Upgma Cluster Analysissupporting
confidence: 75%
“…Para altura da inserção da primeira vagem, as cultivares e linhagens avaliadas foram agrupadas em dois grupos pelo teste de Scott e Knott, em que o grupo com os melhores resultados apresentaram valores de 15,26 a 19,30 cm, e o grupo com menor valor de 11,46 a 11,86. Sendo assim, ambos os grupos apresentam valores aceitáveis para esta característica, uma vez que as estimativas devem ser superiores à 12 cm, para facilitar a colheita mecanizada e diminuir de perdas causadas por doenças fúngicas ocasionadas pelo contato das vagens à umidade do solo (OLIVEIRA et al, 2014;GONÇALVES et al, 2016). O comprimento médio longitudinal das vagens variou 13,75 a 9,25 cm, dividindo as cultivares / linhagens em seis grupos, em que a cultivar Novo Jalo apresentou o melhor resultado de 13,75 cm (Tabela 2).…”
Section: Resultsunclassified
“…Para número médio de vagens por plantas as cultivares e linhagens ficaram divididas em dois grupos, o primeiro com valores de 15,50 a 24,73 e o segundo com melhor resultado de 27,73 a 33,93 vagens por plantas (Tabela 2). O resultado do melhor grupo é superior aos resultados obtidos por Mambrin et al (2015) avaliando 14 linhagens avançadas de feijão e por Gonçalves et al (2016) avaliando 40 acessos tradicionais de feijão.…”
Section: Resultsunclassified
See 1 more Smart Citation